창고 용량 제한 2단계 공급사슬을 위한 로트 사이징 문제 - 황학진; 정호균; 김진학 (한국경영과학회지, 2024)
We consider a two-stage supply chain consisting of a manufacturing facility at the first stage and a distribution center at the second stage of which warehouse space is capacitated. We model the supply chain with a dynamic lot-sizing problem with concave production and transportation costs. A polynomial time algorithm is proposed for this problem.
Keywords: Dynamic Lot-sizing; Storage Capacity; Inventory/Production